PENGARUH JENIS KEMASAN TERHADAP KADAR AIR DAN SUSUT BOBOT MAKANAN TRADISIONAL OLET - Zaki Zulkarnain; Ahmad Mundzir Romdhani; Moh. Nurul Hidayatullah (TAPE : Jurnal Teknologi Hasil Pertanian, 2024)
One of the cultures that Indonesia has is traditional food. Each region has different traditional food and is the hallmark of that area. Olet Cake is a traditional food typical of Sumenep, which is known in the Lenteng sub-district. Olet cake is made from cassava which is mashed and compacted. As a topping, black sticky rice is usually sprinkled on it. However, several factors that support Olet processing are packaging materials for water content and weight loss. There are quite a lot of factors that cause damage to food, including microbial growth and activity, enzyme activity contained in food, parasite activity and water content in food, air, especially oxygen, light and storage time, including the type of packaging. Packaging can inhibit the rate of damage to the product with the parameters of water content and weight loss. The method used in this research uses four packages, namely: Standing pouch, Mica, Banana leaves, Waxed paper. There are two parameters observed in this research. Water content and weight loss. The results of the research showed that there was no real difference in the use of standing pouch packaging, mica, banana leaves and wax paper, on the water content of traditional olet cake snack products. And in the weight loss results obtained there was no significant difference in the use of standing pouch, mica, banana leaf and wax paper packaging.